Biologic Disease-Modifying and Other Anti-Rheumatic Drugs Use in Patients with Moderate-to-Severe Juvenile Idiopathic Arthritis Based on a Japanese Nationwide Claims Database - Hata T; Hirata A; Ota R; Hosohata K; Nishihara M; Neo M; Katsumata T (Therapeutics and Clinical Risk Management, 2022)
Takeo Hata,1 Atsushi Hirata,2 Ryosuke Ota,2 Keiko Hosohata,3 Masami Nishihara,1 Masashi Neo,1 Takahiro Katsumata1 1Department of Pharmacy, Osaka Medical and Pharmaceutical University Hospital, Takatsuki, Osaka, Japan; 2Department of Pharmacy, Kindai University Nara Hospital, Ikoma, Nara, Japan; 3Education and Research Center for Clinical Pharmacy, Osaka Medical and Pharmaceutical University, Takatsuki, Osaka, JapanCorrespondence: Keiko Hosohata, Education and Research Center for Clinical Pharmacy, Osaka Medical and Pharmaceutical University, 4-20-1 Nasahara, Takatsuki, Osaka, 569-1094, Japan, Tel +81-72-690-1271, Fax +81-72-690-1023, Email hosohata@gly.oups.ac.jpPurpose: Biologic disease-modifying anti-rheumatic drugs (bDMARDs) are highly effective and safe against juvenile idiopathic arthritis (JIA), which is classified into systemic JIA (sJIA) and the other JIA categories (non-sJIA) according to differences in clinical symptoms and pathophysiology. The purpose of the current study was to investigate trends in patterns of prescribing bDMARDs for moderate-to-severe JIA using a relatively large sample size in Japan.Patients and Methods: A descriptive epidemiological study based on a nationwide claims database in Japan was conducted from 2012 to 2018 using the “JMDC Claims Database” to explain annual changes based on the number of patients prescribed bDMARDs. Study drugs were identified based on the Anatomical Therapeutic Chemical codes, such as methotrexate, glucocorticoids, non-steroidal anti-inflammatory drugs, and bDMARDs.Results: From a database of 6,862,244 patients, the following exclusion criteria were applied: aged ≥ 16 years, without “M08” in their ICD-10 code as disease, and missing the information of prescription date in the database during the study period, resulting in a final number of 111 JIA patients. We found an increasing trend for adalimumab and tocilizumab and a decreasing trend for methotrexate. Differences in medication use between sJIA and non-sJIA patients were also evident, being consistent with national and international guidelines.Conclusion: Although the introduction of bDMARDs has markedly improved the efficacy of JIA therapy, there are still many short- and long-term safety issues to be examined, including the risk of infection and potential risk of associated malignancy. Future studies are needed to clarify these issues.Keywords: arthritis, juvenile, antirheumatic agents, biological products, database